Atomic‐Layered Cu5 Nanoclusters on FeS2 with Dual Catalytic Sites for Efficient and Selective H2O2 Activation. (21st March 2022) - Ling, Cancan; Liu, Xiufan; Li, Hao; Wang, Xiaobing; Gu, Huayu; Wei, Kai; Li, Meiqi; Shi, Yanbiao; Ben, Haijie; Zhan, Guangming; Liang, Chuan; Shen, Wenjuan; et al.
Abstract: Regulating the distribution of reactive oxygen species generated from H2 O2 activation is the prerequisite to ensuring the efficient and safe use of H2 O2 in the chemistry and life science fields. Herein, we demonstrate that constructing a dual Cu−Fe site through the self‐assembly of single‐atomic‐layered Cu5 nanoclusters onto a FeS2 surface achieves selective H2 O2 activation with high efficiency. Unlike its unitary Cu or Fe counterpart, the dual Cu−Fe sites residing at the perimeter zone of the Cu5 /FeS2 interface facilitate H2 O2 adsorption and barrierless decomposition into ⋅OH via forming a bridging Cu‐O‐O‐Fe complex. The robust in situ formation of ⋅OH governed by this atomic‐layered catalyst enables the effective oxidation of several refractory toxic pollutants across a broad pH range, including alachlor, sulfadimidine, p‐nitrobenzoic acid, p‐chlorophenol, p‐chloronitrobenzene. This work highlights the concept of building a dual catalytic site in manipulating selective H2 O2 activation on the surface molecular level towards efficient environmental control and beyond. Abstract : Dual Cu−Fe catalytic centers situated at the perimeter region of Cu5 /FeS2 facilitate H2 O2 adsorption and barrierless decomposition into ⋅OH through forming a bridging Cu‐O‐O‐Fe structure, thereby realizing selective H2 O2 activation with high efficiency and enabling excellent degradation activities of refractory organic pollutants.